Blend Electrospinning of Nigella sativa-Incorporating PCL/PLA/HA Fibers and Its Investigation for Bone Healing Applications - Moghaddasi, Mohammad; Ozdemir, Muhammed Mustafa Mert; Noshahr, Ali Torabkhani; Ozadenc, Huseyin Murat; Oktay, Busra; Bingol, Ayse Betul; Arayici, Pelin Pelit; Eraslan, Azime; Senel, Ilkay; Chifiriuc, Mariana Carmen; Ustundag, Cem Bulent (AMER CHEMICAL SOC, 2024)
One of the well-known postoperative complications that requires a number of prophylactic and curative treatments is infection. The implications of postsurgical infections are further exacerbated by the emergence of antibiotic-resistant strains. Reduced effectiveness of synthetic antibiotics has led to an interest in plant-based substances. Extracts obtained from Nigella sativa have been shown to possess effective anti-infectious agents against bacteria frequently seen in bone infections. In this study, a fiber-based bone scaffold containing polycaprolactone, poly(lactic acid), and hydroxyapatite with N. sativa oil at varying concentrations was developed. Solvent electrospinning was used to fabricate the fibers with the specified composition. According to FE-SEM analysis, fibers with average diameters of 751 +/- 82, 1000 +/- 100, 1020 +/- 90, and 1223 +/- 112 nm were formed and successful integration of N. sativa oil into the fiber's structure was confirmed via FTIR. Staphylococcus aureus showed moderate susceptibility against the fibers with a maximum inhibition zone diameter of 11.5 +/- 1.6 mm. MTT assay analysis exhibited concentration-dependent cell toxicity against fibroblast cells. In short, the antibacterial fibers synthesized in this study possessed antibacterial properties while also allowing moderate accommodation of CDD fibroblast cells at low oil concentrations, which can be a potential application for bone healing and mitigating postsurgical infections.
Keywords: ANTIBACTERIAL ACTIVITY; CHEMICAL-COMPOSITION; Chemistry